The Language Politeness in The Novel Beauty And The Best by Luna Torashyngu - Mislamuddin, Mislamuddin; Wicaksono, Andri; Alfiawati, Riska; Damiri, Adenan (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2018)
This research aimed to investigate the language politeness in the novel